2008
DOI: 10.1086/591913
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Cleared Episodes of Herpes Simplex Virus Reactivation in Immunocompetent Adults

Abstract: Background Herpes simplex virus (HSV) remains latent in nerve root ganglia of infected persons and is thought to reactivate several times yearly. Recent in situ data show the localization of HSV-specific CD8+ T cells at the dermal epidermal junction next to peripheral sensory nerve endings, suggesting that viral reactivation may occur more frequently than previously appreciated. Methods Twenty-five HSV-2–seropositive and 18 HSV-1–seropositive healthy adults collected anogenital and oral swabs, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
269
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 249 publications
(295 citation statements)
references
References 40 publications
18
269
0
8
Order By: Relevance
“…Moreover, most immune competent individuals experience episodes of oral herpes virus reactivation, but it will last only for few hours or day, which is very less time span to initiate periodontal disease. (31) Association between systemic diseases like cardiac diseases and viruses is still a question. Vascular disease occur at a higher frequency as a result of combined infections with herpes simplex virus and Chlamydia pneumonia.…”
Section: Herpesvirus Bacterial Interactions In Periodontitismentioning
confidence: 99%
“…Moreover, most immune competent individuals experience episodes of oral herpes virus reactivation, but it will last only for few hours or day, which is very less time span to initiate periodontal disease. (31) Association between systemic diseases like cardiac diseases and viruses is still a question. Vascular disease occur at a higher frequency as a result of combined infections with herpes simplex virus and Chlamydia pneumonia.…”
Section: Herpesvirus Bacterial Interactions In Periodontitismentioning
confidence: 99%
“…11,12 Recent data suggest that HSV reactivation may occur much more frequently than previously understood, and may be characterised by frequent short bursts of viral shedding that do not correlate with symptoms. 13 As HSV-2 seroprevalence decreased, HSV-1 seroprevalence in the USA increased to 62% in 1988-94 from 57.7% in 1999-2004. 2 Among persons infected with HSV-1 but not HSV-2, a higher percentage reported a diagnosis of genital herpes in 1999-2004 compared with 1988-94 (1.8% versus 0.4%).…”
Section: Epidemiology Of Genital Herpesmentioning
confidence: 99%
“…HSV was previously thought to be in the latent state most of the time during chronic infection, with rare clinically evident reactivation episodes, conceptually similar to varicella zoster virus (VZV). However, shedding studies using anogenital swabs collected by HSV-2-seropositive persons once or multiple times daily for viral culture or for quantitative real-time PCR have revealed that HSV and the host are in constant conflict, with frequent HSV reactivation and rapid clearance (31). This implies host responses that likely involve cell-intrinsic and -extrinsic mechanisms of innate as well as acquired immunity.…”
Section: Introductionmentioning
confidence: 99%